Differential screening reveals genes differentially expressed in low- and high-virulence near isogenic Phytophthora sojae lines - Ziying, W.; Yuanchao, W.; Xiaoren, C.; Gui, S.; Zhengguang, Z.; Xiaobo, Z.
To explore the molecular mechanisms involved in virulence variations in Phytophthora sojae, the low-virulence isolate PS2 was inoculated successively on a resistant soybean (Glycine max)cultivar. After 14 successive inoculations, a high-virulence progeny, termed PS2- vir, was obtained and demonstrated to exhibit lower oospore production. DNA Wngerprinting revealed no large-scale DNA diVerences in PS2 and PS2-vir. A suppression subtractive hybridization (SSH)approach was developed to investigate diVerences in gene expression between PS2 and PS2-vir in the early stages of soybean infection. Of the 323 sequences chosen for examination, 74 utative unigenes were identiWed that exhibit high expression in PS2-vir. These sequences are predicted to encode proteins involved in energy production, protein biosynthesis, cell signaling, cell-wall biogenesis, and transcription regulation. Ten clones were selected for temporal expression analysis using RT-PCR based on the results of the dot-blot screens. The possible genetic mechanisms involved in these phenomena are discussed.
Keywords: PHYTOPHTHORA SOJAE; TRANSCRIPTION REGULATION; VIRULENCE VARIATION; OOSPORE PRODUCTION